Penentuan Percepatan Gravitasi Bumi Menggunakan Bandul Sederhana Di Daerah Kampus UPI - Khairul Sabri; Nanda Aisyah Kurniati; Dzulfikar Nasriyan Fadhilah; M Dearil Ardiansyah (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Many people assume that the value of gravitational acceleration always has a fixed value. However, if we look closely, the value of gravitational acceleration always changes in each place. This research aims to compare differences in Earth's gravitational acceleration in various locations. Through this research, researchers can identify the causes of differences in gravity, one of which is differences in height. The method used in this research is a simple pendulum experimental method, with a quantitative approach to collecting data from various places. The results obtained for g in the JICA building on the 5th floor were 9,47 m/s², g in the FIP building on the 10th floor was 9,72 m/s², g in the FPTK 9,59 m/s², and g at the National Museum of Education is 9,72 m/s². Apart from that, it can be found the average magnitude of the gravitational acceleration from these four places is 9,62 m/s². From these results it can be concluded that the magnitude of the Earth’s gravitational acceleration is different in each place. Apart from height, this difference can also occur due to uncertainty in measuring gravity.